Menegakkan Syariah Compliance dalam Pasar Modal Syariah - Agus Triyanta (Fakultas Hukum Universitas Islam Indonesia, 2004)
In view of common people, every financial institution is almost called as a bank, and their image about bank is creditor, and the creditor is usury. Based on this assumption, the breakthrough opening syariah (Islamic law) stock exchange in which it is far from the usury and the substance of proscribed. Itis the handicaps for all Islamic business as well as the appropriate moment to wake the Moslem consciousness an the importance and legality of business through investment and as the other alternative of the economic system.